The Use of Audio Media vs. Audio-Visual Media in Teaching Listening - Nindiyana, Ayu (RETAIN, 2020)
Listening is the activity of receiving the information from the speaker, interpreting the meaning, and giving responds. In listening activity, there are two media that are commonly used, audio media which provides audio only and audio-visual media which provides audio and visual. This research is to compare which is more effective to improve students’ understanding, audio media or audio-visual media. This research used quantitative method with quasi-experimental design. It conducted in one of public vocational school with two classes of tenth. The researcher used test (pre-test and post-test) to collect the data. The result of the research showed that there was difference between audio media and audio-visual media. The asymptotic significance of post-test was .012 < .05 with the median of audio media was 68.00 and audio-visual media was 74.00. It meant that the mean of audio-visual media was higher than audio media. Keywords: Listening, Audio Media, Audio-Visual Media.